2003
DOI: 10.1007/s10120-003-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

A new scoring system for peritoneal metastasis in gastric cancer

Abstract: tumor, and resection of peritoneal tumor were independent factors to predict prognosis. Conclusion. These results showed that the volume scoring system was strongly related to the prognosis, and the patients assessed as Gr I had a great probability of cure by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Peritoneal metastasis (PM) occurs in more than 50 % of patients with unresectable and recurrent gastric cancer through their clinical course, and it causes various complications, such as ascites, intestinal stenosis, hydronephrosis, and obstructive jaundice; the prognosis of patients with severe PM is dismal and generally worse than that of those without PM [8]. The Japan Clinical Oncology Group (JCOG) conducted a randomized phase III study (JCOG0106) of 5-fluorouracil (5-FU) continuous infusion (5-FUci) versus sequential methotrexate (MTX) and 5-FU therapy in patients having AGC with PM and concluded that 5-FUci, which is one of the most feasible regimens, is the standard first-line chemotherapy for such patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal metastasis (PM) occurs in more than 50 % of patients with unresectable and recurrent gastric cancer through their clinical course, and it causes various complications, such as ascites, intestinal stenosis, hydronephrosis, and obstructive jaundice; the prognosis of patients with severe PM is dismal and generally worse than that of those without PM [8]. The Japan Clinical Oncology Group (JCOG) conducted a randomized phase III study (JCOG0106) of 5-fluorouracil (5-FU) continuous infusion (5-FUci) versus sequential methotrexate (MTX) and 5-FU therapy in patients having AGC with PM and concluded that 5-FUci, which is one of the most feasible regimens, is the standard first-line chemotherapy for such patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…( 1 ) The most frequent cause of death of gastric cancer patients is peritoneal metastasis, which is difficult to diagnose preoperatively and to cure completely by surgery or chemotherapy. ( 2 ) Therefore, the development of new therapeutic/preventive strategies for peritoneal metastasis of gastric cancer is desired.…”
mentioning
confidence: 99%
“…• local unresectability (because of infiltrating tumor growth into relevant neighboring anatomical structures), • hepatic or other distant metastases, • tumor growth within more distant lymph nodes or • peritoneal tumor spread [6,10].…”
Section: Methodsmentioning
confidence: 99%
“…A significantly longer survival time has been seen (10.5 vs. 6.7 months) in the case of only one criterion of unresectability, whereas median survival time did not significantly differ in the case of two or three sites of metastatic tumor growth [10]. The ''Japanese Research Society for Gastric Cancer'' tried to differentiate the various extent of peritoneal tumor growth for the first time in 1995 by subdividing the peritoneal tumor spread into various stages of peritoneal carcinomatosis (P0-P3) [6]. However, despite multiple modifications, this classification has only achieved limited importance in clinical research because of its ambiguity and difficult use in daily clinical practice.…”
Section: Perioperative Morbidity and Mortalitymentioning
confidence: 97%
See 1 more Smart Citation